Palaeoenvironments and plant availability during MIS 6 to MIS 3 on the edge of the Palaeo-Agulhas Plain (south coast, South Africa) as indicated by phytolith analysis at Pinnacle Point. (1st May 2020) - Esteban, Irene; Marean, Curtis W.; Cowling, Richard M.; Fisher, Erich C.; Cabanes, Dan; Albert, Rosa M.
Abstract: The Cape south coast presents some of the world's most significant early modern human sites preserving evidence for complex human behaviour during the Middle Stone Age (MSA), and it is centrally located in the megadiverse Greater Cape Floristic Region. The extinct Palaeo-Agulhas Plain (PAP) once abutted this region, forming an important habitat for the subsistence strategies of past hunter-gatherers during the MSA. Here, we use phytoliths — amorphous silica particles that formed in cells of plants — extracted from archaeological deposits of two sites at Pinnacle Point (PP; cave 13B [PP13B] and site 5–6 [PP5-6]) to investigate the interactions between environments and hunter-gatherer foraging strategies along the Cape south coast during Marine Isotope Stage (MIS) 6 to MIS 3. To do this, we developed an analytical approach built on a modern plant and soil reference collection for using phytoliths from archaeological deposits for palaeoenvironmental reconstructions. In the latter phases of MIS 6, phytoliths indicate shrubby vegetation, possibly limestone fynbos, which might have occurred in inland landscapes, and this was the area preferred for plant foraging practices by the inhabitants of PP13B. During MIS 4, phytoliths at PP5-6 indicate the presence thicket and riparian vegetation on the rocky cliffs and the exposed PAP, along with some type of fynbos vegetation above the actual coastal cliffs. During interglacials MIS 5(c-e) and MIS 3 when the PAP was less exposed, the phytolith record points towards a mosaic of habitats with fynbos and thicket/forest, but also a constant presence of vegetation with high grass content dominated by a mix of both C3 and C4 species. Our data suggests a continuous inland regional mosaic of habitats with fynbos, thicket/forest and grassy vegetation that persisted during the glacial-interglacial periods. The changes observed in the phytolith record might be indicative of changes in plant foraging preferences along with slight vegetation movements in accordance with climate changes and sea level fluctuations. Highlights: Phytoliths can infer vegetation types distribution along the Cape south coast. Phytoliths were considered a merged product of human behaviour and local vegetation. Thicket and riparian were the most preferred vegetation types foraged for firewood. Regional mosaic habitats were present at Pinnacle Point over time. The Cape south coast experienced rapid biome shifts during the Pleistocene.